2019
DOI: 10.1093/cesifo/ifz005
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Private for-Profit Hospital Ownership on Costs and Quality of Care – Evidence from Germany

Abstract: What is the impact of private for-profit (PfP) hospital ownership on costs and quality of care? In light of a substantial and increasing share of PfP hospitals in many hospital markets like the USA or Germany, this is an important question. We estimate the effect of PfP ownership on hospital 30-day- and 1-year-mortality outcomes and hospital costs by focusing on heart attacks and pneumonia, two very common conditions in healthcare markets. We use rich administrative hospital data from Germany for the years 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…For example, some studies nd that mortality rates [37] and the likelihood of dying [38] are lower in private sectors. Another study also found lower 30-day-mortality rates for pneumonia patients in private hospitals [21]. While, the rates of 30-day all-cause rehospitalizations of older patients are higher in private hospitals than public hospitals [39].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…For example, some studies nd that mortality rates [37] and the likelihood of dying [38] are lower in private sectors. Another study also found lower 30-day-mortality rates for pneumonia patients in private hospitals [21]. While, the rates of 30-day all-cause rehospitalizations of older patients are higher in private hospitals than public hospitals [39].…”
Section: Discussionmentioning
confidence: 90%
“…While, a few studies have found private hospitals may provide health care services with better quality. For instance, Wüber and Wuckel (2019) [21] nd lower 30-day-mortality rates in private hospitals in Germany. As the variations in hospital quality measurements are great, the impacts of private ownership vary across different countries.…”
Section: Private Hospitals and Health Care Qualitymentioning
confidence: 99%
“…On the one hand, private hospitals might be more responsive to patients needs compared to public hospitals, which might be an important source of improved quality and productivity in hospital markets (see Wübker and Wuckel, for a discussion of the literature). 15 What is more, PfP might improve quality by adopting performance-improving innovation, particularly if combined with increased competition. 16 On the other hand, private hospitals may be more prone to compromise patient outcomes compared to public hospitals because information assymetries might allow hospitals to cut costs at the expense of hard-to-monitor/measure quality areas.…”
Section: Pro-competetive Reformsmentioning
confidence: 99%